2019
DOI: 10.1038/s41598-019-48840-8
|View full text |Cite
|
Sign up to set email alerts
|

EXTL3-interacting endometriosis-specific serum factors induce colony formation of endometrial stromal cells

Abstract: Endometriosis is a benign chronic condition characterized by the existence of endometrial-like stroma and glandular tissue in extrauterine locations. The molecular mechanisms of its pathogenesis have not been elucidated. We have studied the role of EXTL3 (exostosin-like 3) in endometriosis and found that it is expressed in endometrial tissue as well as endometriosis lesions. We have found that serum from endometriosis patients contains a factor or factors, which interact with EXTL3 resulting in strongly increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The involvement of EXTL3 in endometriosis, a benign chronic condition characterized by the existence of endometrial-like stroma and glandular tissue in extrauterine locations, was recently reported [46]. Unidentified factor(s) in the serum of patients interacted with EXTL3, resulting in increased colony formation in regenerating cell cultures.…”
Section: Novel Function Of Extl3 As a Cell Surface Receptormentioning
confidence: 95%
“…The involvement of EXTL3 in endometriosis, a benign chronic condition characterized by the existence of endometrial-like stroma and glandular tissue in extrauterine locations, was recently reported [46]. Unidentified factor(s) in the serum of patients interacted with EXTL3, resulting in increased colony formation in regenerating cell cultures.…”
Section: Novel Function Of Extl3 As a Cell Surface Receptormentioning
confidence: 95%